Patterns and correlates of accelerometer-assessed physical activity and sedentary time among colon cancer survivors - Lynch, B.; Boyle, Terry; Winkler, E.; Occleston, J.; Courneya, K.; Vallance, J. (Kluwer Academic Publishers, 2016)
Background: Understanding of the physical activity and sedentary behavior of cancer survivors is limited by reliance on self-reported data. Here, we report the correlates, and patterns of accumulation, of physical activity (light, and moderate-vigorous; MVPA) and sedentary behavior, in colon cancer survivors, using accelerometer-based assessments. Methods: Colon cancer survivors from Alberta, Canada (n = 92), and Western Australia (n = 93) (overall response rate = 21 %) wore an Actigraph® GT3X+ accelerometer for seven consecutive days and completed a questionnaire in 2012–2013. Accelerometer data (60 s epochs) were summarized using Freedson activity cutpoints and were adjusted for wear time. Linear regression analyses, conducted 2014–2015, examined correlates for different intensities of activity. Results: Younger age, being employed, higher family income, and lower BMI were significantly correlated with MVPA, while gender, educational attainment, and BMI were correlated with light-intensity physical activity. Gender, comorbidities, and BMI were correlated with sedentary time. MVPA did not vary by day of the week, whereas the remaining time (as a sedentary/light ratio) showed significant variation, with Saturdays being more sedentary than average. When considering time of day, we found that evenings were when the likelihood of both MVPA and sedentary time was highest. Conclusions: The low level of MVPA and high volume of sedentary time demonstrated by these objective data highlight the need for intervention in colon cancer survivors. The correlates and accumulation patterns described by this study may better inform interventions and translational research designed to increase physical activity and reduce sedentary behavior in colon cancer survivors.